Genetic advance and heritability for tuber yield and its component characters in Sweet potato - Afolabi, Michael Segun (Journal of Pure and Applied Agriculture, 2023)
Knowledge of the magnitude of genetic variability, heritability and genetic gains in selection of desirable characters could assist the plant breeder in ascertaining criteria to be used for the breeding programmes. Thirty sweetpotato genotypes were evaluated at the Teaching and Research farm, Osun State University, Ejigbo, Osun State, Nigeria, during 2018 and 2019 cropping seasons to estimate genetic variability, heritability and genetic advance of tuber yield and its component characters. Planting of 25 cm long vine was inserted at a slant, with two-third buried below the soil surface. Weeding was done 4, 6 and 8 weeks after planting, using small hoes. No herbicides or fertilizers were applied. Data were recorded on percentage of survival after 2 weeks, no of tubers per plant, tuber weight per plant, fresh tuber yield, vine length at 8 weeks after planting, foliage weight at harvest. Results show that the effect of genotype and genotype by year interaction were significant for tuber weight per plant and fresh tuber yield, while the effect of year was highly significant (P< 0.01) for all the characters. High magnitude of phenotypic and genotypic coefficient of variations as well as high heritability along with high genetic advance recorded for tuber yield, number of tubers per plant, vine length and fodder weight provide evidence that these parameters were under the control of additive gene effects and effective selection could be possible for improvement for these characters. The most outstanding accessions (Ex-Igbariam, Bath, W-151, Offa 2, Mothers delight and Ojo oba) for tuber yield could be sources of alleles that can be manipulated with other promising cultivars for higher tuber yield. © 2022 Department of Agricultural Sciences, AIOU